Noncanonical Matrix Metalloprotease 1–Protease-Activated Receptor 1 Signaling Drives Progression of Atherosclerosis. Issue 6 (June 2018) - Rana, Rajashree; Huang, Tianfang; Koukos, Georgios; Fletcher, Elizabeth K.; Turner, Susan E.; Shearer, Andrew; Gurbel, Paul A.; Rade, Jeffrey J.; Kimmelstiel, Carey D.; Bliden, Kevin P.; Covic, Lidija; Kuliopulos, Athan
Abstract : Objective—: Protease-activated receptor-1 (PAR1) is classically activated by thrombin and is critical in controlling the balance of hemostasis and thrombosis. More recently, it has been shown that noncanonical activation of PAR1 by matrix metalloprotease-1 (MMP1) contributes to arterial thrombosis. However, the role of PAR1 in long-term development of atherosclerosis is unknown, regardless of the protease agonist. Approach and Results—: We found that plasma MMP1 was significantly correlated ( R =0.33; P =0.0015) with coronary atherosclerotic burden as determined by angiography in 91 patients with coronary artery disease and acute coronary syndrome undergoing cardiac catheterization or percutaneous coronary intervention. A cell-penetrating PAR1 pepducin, PZ-128, currently being tested as an antithrombotic agent in the acute setting in the TRIP-PCI study (Thrombin Receptor Inhibitory Pepducin-Percutaneous Coronary Intervention), caused a significant decrease in total atherosclerotic burden by 58% to 70% ( P <0.05) and reduced plaque macrophage content by 54% ( P <0.05) in apolipoprotein E–deficient mice. An MMP1 inhibitor gave similar beneficial effects, in contrast to the thrombin inhibitor bivalirudin that gave no improvement on atherosclerosis end points. Mechanistic studies revealed that inflammatory signaling mediated by MMP1–PAR1 plays a critical role in amplifying tumor necrosis factor α signaling in endothelial cells. Conclusions—: These data suggest that targeting the MMP1–PAR1 system may be effective in tamping down chronic inflammatory signaling in plaques and halting the progression of atherosclerosis. Abstract : Supplemental Digital Content is available in the text.